Utilization of Lerak Juice (Sapindus rarak DC) as Natural Surfactant in the Liquid Washing Soap Production - La Choviya Hawa; Naura Lulu Farhanrika; Ary Mustofa Ahmad (The University of Lampung, 2022)
Before detergent was commonly used, a natural cleanser which function is to help people to clean several things in their houses was Lerak berry (Sapindus Rarak DC). This berry contains saponins (28%) which can be used as the ingredient for shampoo, soap, and other kind of cleaning agents. Dilutting Lerak juice into soap base will produce liquid washing soap which can be an alternative to reduce the use of detergents. This study aims at finding the best treatment, balance ratio of Lerak juice (2:1; 3:2; 1:1; 2:3), and diluting method for the soap base (heating and non-heating) to be used for producing liquid washing soaps with the best characteristic. This study uses two-factor randomized block design method which later be analyzed using ANOVA. Organoleptic testing of the hedonic quality to the color, scent, foam quantity, cleaning-power, the after-effects impression, and the general assessment of the liquid washing soaps results a 2:1 Lerak juice balance ratio with heating method is found to be the best treatment for diluting method. The balance ratio affects the consistency and viscosity which also affects the density, pH, and water holding capacity, but does not affect the foam’s stability. Keywords: Lerak, Liquid Washing Soap, Sapindus Rarak, Surfactant